2017
DOI: 10.1093/cercor/bhw412
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Egomotion-Consistent Optic Flow in the Rhesus Macaque Cortex

Abstract: The cortical network that processes visual cues to self-motion was characterized with functional magnetic resonance imaging in 3 awake behaving macaques. The experimental protocol was similar to previous human studies in which the responses to a single large optic flow patch were contrasted with responses to an array of 9 similar flow patches. This distinguishes cortical regions where neurons respond to flow in their receptive fields regardless of surrounding motion from those that are sensitive to whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(83 citation statements)
references
References 82 publications
10
72
0
Order By: Relevance
“…Bremmer et al (2001), a multisensory area that integrates visual and vestibular inputs Schlack et al, 2002;Chen et al, 2011). In particular, VIP in macaque strongly responds to optic flow (Cottereau et al, 2017) and is supposed to play an important role for navigation in space (Bremmer, 2005). Altogether, these results are in line with our findings and suggest that area VIP is important for locomotion in both human and macaque.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Bremmer et al (2001), a multisensory area that integrates visual and vestibular inputs Schlack et al, 2002;Chen et al, 2011). In particular, VIP in macaque strongly responds to optic flow (Cottereau et al, 2017) and is supposed to play an important role for navigation in space (Bremmer, 2005). Altogether, these results are in line with our findings and suggest that area VIP is important for locomotion in both human and macaque.…”
Section: Discussionsupporting
confidence: 92%
“…Its responses are strongly influenced by optic flow signals but are not modulated by inertial motion (Fan et al, 2015). If areas V6 in human and macaque share similar visual properties, like their retinotopic organization (Pitzalis et al, 2006; or their selectivity to optic flow (Cardin and Smith, 2010;Fan et al, 2015, but see Cottereau et al, 2017), our results suggest that human V6 has a specific role for processing locomotion consistent vestibular inputs. It is, therefore, possible that the homology between human and macaque V6 is not as pronounced as currently believed (Pitzalis et al, 2013;2015).…”
Section: Discussionmentioning
confidence: 72%
“…If, however, biases remain as large as they are under simulated pursuit, that finding would suggest that downstream areas integrate efference-copy cues. Relatively few physiological studies have investigated pursuit compensation in frontal (Yang and Gu, 2017), premotor (Cottereau et al, 2017), or high-level parietal (Siegel and Read, 1997) cortical areas that receive projections from high-level visual-motion cortex. Additional investigations into the roles of efference copy in these areas would therefore benefit the field.…”
Section: Relationship With Human Psychophysical Literaturementioning
confidence: 99%
“…Prior to our statistical analyses, we used independent datasets to characterise the BOLD haemodynamic impulse response functions (HRF) separately for each animal. These datasets respectively contained 16 (M01) and 12 (M02) 204s long runs that consisted of 6 cycles of 4s full field counter phasing (10Hz) checkerboards separated by a 30s blank interval (see more details about this procedure in Cottereau et al, 2017). Data were pre-processed using the pipeline described above and projected onto individual surfaces generated with the CARET software (Van Essen et al, 2001).…”
Section: Hrf Estimationmentioning
confidence: 99%
“…Finally, it is worth noting that in monkey M02, significant BOLD activations were also found in more anterior parts of the IPS (p<10 -3 , uncorrected, see figures 2, 3 and 4), notably within the ventral and anterior intraparietal areas (VIP and AIP, respectively). VIP has been shown to be involved in egomotion-compatible optic flow processing in both monkey (Cottereau et al, 2017) and human (Wall & Smith, 2008), whereas AIP has been suggested to play a role in 3D object processing and visually guided hand movements in both species as well (Sakata et al, 1997;Durand et al, 2007;Shikata et al, 2007). Unfortunately, we were not able to find those activations in the other macaque, potentially because of a slightly smaller SNR.…”
mentioning
confidence: 99%